Expertise and offending: Themes for future research. (January 2015) - Nee, Claire; Ward, Tony
Abstract: In this final article, we note how the expertise paradigm has allowed us to assess the psychological processes involved in experienced decision-making in a relatively precise and micro-analytical way, in both deviant and non deviant contexts. We note that expert decision-making involves the increasingly fast and automatic recognition, over time and repeated exposure, of environmental cues relevant to a domain of expertise. In turn, these cues trigger a range of routine and habitual behavioral scripts, rapidly and unconsciously chosen from mental schemas rich with information about what has worked in the past, and which is responsive to changing environments. All of the reviews in this special issue have found evidence suggesting that these processes are at work in the mind of the offender within the crime facilitative environments. We note the continuum of expertise in offenders redolent of expertise in general, and highlight the idea of encouraging offenders to use expertise related skills such as enhanced problem solving, in pro-social ways. We note the significant gaps in knowledge that this issue has illuminated in relation to practice, consciousness and individual differences, and suggest that research using simulations may make a considerable contribution to understanding offending behavior.